Tassoni and the burlesque literature of XVI century (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2022)
The paper outlines the fraught relationship between Alessandro Tassoni, founder of the ‘eroicomico’, and the comic poetry of the first half of the 16th century, dwelling in particular on the possible influence that Francesco Berni, the father of ‘burlesco’, may have had on Tassoni’s production. The analysis of Tassoni’s self-exegetic writings (declarations and prefaces) allows us to distinguish poetic pronouncements from actual textual realisations, as regards to Tassoni’s satirical poetry, a genre in which the lesson of the 16th-century masters (Berni for first) is substantial.
Keywords: Alessandro Tassoni; Francesco Berni; heroicomic; burlesque poetry; 17th century